Modelling and Analysis of Post-occupancy Behaviour in Residential Buildings to Inform BASIX Sustainability Assessments in NSW. (2017) - Samaratunga, Marini; Ding, Lan; Bishop, Kate; Prasad, Deo; Yee, Kevin W.K.
Abstract: Sustainability assessment tools aim to promote high sustainability outcomes in residential buildings, ensuring less consumption of water, energy and less emission of greenhouse gases. However, existing literature often presents variations between the estimated outcomes from the assessment tools and actual outcomes after building occupation. Research suggests that actual energy consumption could be significantly influenced by resident behaviour in addition to the dwelling conditions and the energy efficiency of appliances. This qualitative study explores the nature of resident behaviour in achieving thermal comfort and how these influence the actual energy performance of BASIX-affected dwellings in NSW. A preliminary evidence-based behaviour model is developed to support the behavioural analysis. The model positions the heating and cooling effects of the dwellings' design, the behaviour of residents in space heating and cooling, hot water consumption, etc. as well as multiple influential attributes such as resident's perceptions, preferences, attitudes and knowledge towards energy efficiency in relationship to energy efficiency outcomes. The model not only identifies the key drivers that trigger energy consumption behaviour, but also investigates the potential inter-relationships among all the key influential attributes. The findings of this research will inform the BASIX assessment tool, sustainability policy, building designs and government educational programs on sustainability.